A mística islâmica em Terræ Brasilis: o sufismo e as ordens sufis em São Paulo - Silva Filho, Mário Alves da (2012)
This research has, by scope, to present Tasawwuf (Arabic word that refers to mysticism and Islamic esotericism), known in the West as Sufism and discuss their presence in Brazil in general, specifically in Sao Paulo. Our aim is to try to discuss the presence of Sufism in our country, taking stock of the relationship between the Muslim Sufis with the communities in which they live. We will attempt to demonstrate the presence of Sufism and Sufi orders since the time of slavery to present day. Pointing the presence of Sufi orders that exist today in Sao Paulo. Sufism is a very current issue, being necessary to know and understand it. We see daily the critical irascible behavior of some Muslim communities, but little or no news about Sufism and its active role in Islamic communities, especially as a counterpoint to his irascible behavior pointed. This gap is what we will try to fill. We will discuss Sufism by an exclusively Muslim bias, ie , completely inserted in the universe of Islam. The research will consist of free observing Sufi Orders and open interviews of those responsible for them. We were able to identify nine Sufi Orders in Sao Paulo, and seven of them were described